PENGGUNAAN METODE PROJECT BASED LEARNING UNTUK MENGASAH KETERAMPILAN WRITING DALAM PEMBELAJARAN BAHASA INGGRIS - Zamzam Mustofa; Amir Mukminin; Lika Fikana Putri; Lucky Rosita; Lutfiani Azhari; Luvi Rahma Septiani (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
The use of the Project Based Learning Learning Method is very suitable for use because it involves students using reasoning to improve critical thinking, making decisions about problem solving through active participation, analysis, evaluation, and identification of sources for problem solving, especially in improving writing skills. The writing of this article uses a qualitative descriptive research method. Some of the techniques used in Project Based Learning include (1) analyzing students, (2) determining learning objectives, (3) choosing media and materials, (4) using media and materials, (5) encouraging student participation, and (6) evaluation and improvement. In its application to develop students' writing skills at MAN 3 Madiun, the teaching teacher gives writing tasks in the form of compiling or copying sentences and stringing sentences into a paragraph until it becomes a complete text according to the specified theme. As we know that each student has a different level or proficiency in English mastery, which of course will affect learning.